Quality Matters More Than Quantity: Parent–Child Communication and Adolescents’ Academic Performance - Zhang, Yue (Frontiers in Psychology, 2020)
This study examined the effects of parent-child communication, including the quantitative and qualitative aspects of these communications, on young American adolescents’ academic performance by using an ECLS-K dataset. We considered children’s self-concept a mediator in examining the effects. Structural equation modeling (SEM) was used for evaluating the model. The results revealed that the quality of parent-child communication was positively associated with these children’s academic performance and this association can be mediated by the adolescents’ self-concept. However, the quantity of parent-child communication did not show a direct or an indirect association with the adolescents’ academic achievements. These findings suggest that efforts to improve the quality of parent-child communication and to strengthen the connection between high-quality communications and adolescents’ self-concept may benefit young adolescents’ academic development.